Desde Argentina la reincorporación a España de emigrantes españoles y sus descendientes con doble nacionalidad - Elda González Martínez (Les Cahiers ALHIM)
Since the last decades of the past Century Spain became the country of destination for many immigrants, including Argentinians. Many of them were descendants of Spaniards who recovered their ancestors’ nationality. Therefore they were “returning” Spaniards, even though many of them had never set foot in Spain before. In this paper we analyze the caracteristics of these /returnees/, and the motivations that caused them to move to this country.